Multi Layered-Hierarchal Satellite System - Husár, M.; Volner, R. (Elektronika ir Elektrotechnika, 2010)
Satellites will continue play a major role in the implementation of the Next Generation Internet (NGI). In term of defensibility of contemporary satellite systems it is necessary to make their working more effective. This thesis is about the new conception of satellite systems (particular about multilayered / hierarchal satellite networks). The purpose of my thesis is to analyze the architecture of such networks and to describe and compare actually proposed routing protocols for these systems. I also deal with advantages (and disadvantages) of multilayered satellite systems. Ill. 5, bibl. 5 (in English; abstracts in English, Russian and Lithuanian).